PENGATURAN DAN TANGGUNG JAWAB NOTARIS TERHADAP PENYIMPANAN MINUTA AKTA FIDUSIA DI KOTA PEKANBARU - Khekhe Nadea; Zainul Daulay; Rembrandt Rembrandt (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
A notary is a public official who is authorized to make authentic deeds and has other authorities including those referred to in UUJN. One of the Notary's authorities is to make a fiduciary guaranteed deed, which has been explained in Article 5 UUJF. In connection with this authority, the Notary is required to keep the minutes of the fiduciary deed, one of which is the deposit of the minutes of the fiduciary deed. The problem that occurs at this time is that some Notaries experience difficulties in storing minutes of fiduciary deeds, because there are no clear rules relating to these deposits. With the number of deeds that are made and keeping the minutes of the deed as a Notary protocol can cause problems. The notary may violate existing rules regarding the making of a fiduciary deed and experience problems in storing the number of minuta of this fiduciary deed. Based on this, the authors formulate the problem, namely first, how are the arrangements and responsibilities of a Notary for the storage of minutes of fiduciary deeds, secondly, what are the obstacles in storing the number of minutes of fiduciary deeds. This study uses a juridical-empirical approach. Based on the results of research on the arrangements and responsibilities of a Notary for the safekeeping of minutes of fiduciary deeds, it has been proven that many Notaries violate the rules regarding limiting the number of deed made per day and the Notary is only responsible to the extent of keeping the deed as a Notary protocol, so that if the guarantee time in the deed runs out, The notary keeps it and it is one of the factors in the accumulation of minutes of the deed. In storing the minutes of the fiduciary deed there are several obstacles such as the quality of paper that is easily damaged, making a special cupboard and a large room.